JOB PERFORMANCE EVALUATION MANAGEMENT MODEL UNDER THE SKILLS APPROACH IN COMPANIES OF SERVICES - Díaz, Noiraly (Revista Arbitrada Formación Gerencial, 2024)
The research was oriented to analyze the labor performance evaluation management model under the competence approach, used by Wide Tecc Laboratory, C.A. The type of research is analytical, with a transactional, non experimental and field design. A population census was used, made up of 26 workers from the same organization. Two instruments of data collection were designed, instruments were applied, first a questionnaire containing 28 items, and the second one called an expert panel, according to the twenty-nine (29) competencies defined by D’Anzorena (1997). For the validity of one of the instruments, there was the support of five (05) experts in the content area as  well as in the methodology. It is concluded that if there is an evaluation model for performance, however, it is not the most appropriate according to the results obtained.